Peningkatan Ketepatan Smash Bola Voli Dengan Metode Target Games Pada Siswa Kelas XI SMA Darul Hikmah Tahunpelajaran 2017/2018 - Hermansyah Hermansyah; Andi Gilang Permadi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2018)
The problem revealed in this study is "Improving the Accuracy of Smash in Volleyball with The Games Target Methods at The Second Grade Students of Darul Hikmah in Academic Year 2017/2018" This research was motivated by the still low ability of smash accuracy at the second-grade students of Darul Hikmah. This research is Classroom Action Research (Classroom Action Research) which is carried out collaboratively and participative. The design of this study used Kurt Lewin's model in 2 cycles and in each cycle, there are 2 meetings consist of planning, implementation, observation, and reflection. The research subjects were 30 students of the second-grade students in Darul Hikmah. The results of this study indicate that increased the accuracy of smash in volleyball with the game target method for the second grade of Darul Hikmah. From the results of evaluation in cycle I, the total of students completed = 18 people (60%) and incomplete = 12 people (40%) with the less satisfied category (60%). In cycle II, there was an increase, the total of students completed = 27 people (90%) and incomplete = 3 people (10%). This shows that the results are 90% complete with very good categories